2018
DOI: 10.3389/fcimb.2018.00409
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Antiamebic Compounds That Inhibit Cysteine Synthase From the Enteric Parasitic Protist Entamoeba histolytica by Screening of Microbial Secondary Metabolites

Abstract: Amebiasis is caused by infection with the protozoan parasite Entamoeba histolytica. Although metronidazole has been a drug of choice against amebiasis for decades, it shows side effects and low efficacy against asymptomatic cyst carriers. In addition, metronidazole resistance has been documented for bacteria and protozoa that share its targets, anaerobic energy metabolism. Therefore, drugs with new mode of action or targets are urgently needed. L-cysteine is the major thiol and an essential amino acid for prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Compound 36 showed antiacetylcholinesterase activity and weak anticoagulant activity with PT at 16.8 s [10]. Mori et al also found compounds 1 and 51 showed antiamebic activities in the cysteine-deprived medium, in comparable to in the cysteine-containing medium [24]. In addition, compounds 66, 67, 68, 71, and 72 showed significant anti-HIV activities, with EC 50 values ranging from 0.11 to 0.55 μmol/L and selectivity index values ranging from 12.33 to 75.42 [11].…”
Section: Other Activitiesmentioning
confidence: 92%
“…Compound 36 showed antiacetylcholinesterase activity and weak anticoagulant activity with PT at 16.8 s [10]. Mori et al also found compounds 1 and 51 showed antiamebic activities in the cysteine-deprived medium, in comparable to in the cysteine-containing medium [24]. In addition, compounds 66, 67, 68, 71, and 72 showed significant anti-HIV activities, with EC 50 values ranging from 0.11 to 0.55 μmol/L and selectivity index values ranging from 12.33 to 75.42 [11].…”
Section: Other Activitiesmentioning
confidence: 92%
“…Only four of these enzymes have been the target of significant medicinal chemistry efforts, either in enteric bacteria or in Mycobacterium tuberculosis : O -acetylserine sulfhydrylase isozymes A and B (CysK/CysM) [35,36,37,40,41], phosphoadenosine phosphosulphate reductase (CysH) [38], and serine acetyltransferase (CysE) [42]. Although medicinal chemistry campaigns have successfully led to the discovery of very potent enzyme inhibitors [17,29], the translation of these inhibitors to molecules with antibacterial activity requires more effort [37,38,40]. One important aspect of the cysteine metabolism is the ability of some enzymes of the pathway, namely CysK, CysE, ATP sulfurylase (CysD) and CysD-associated GTPase (CysN), to form complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Although diacetyl kinamycin C and nanaomycin A have been found to be good inhibitors of CS, their use is not feasible for the treatment of amebiasis owing to their toxicity ( Mori et al., 2015 ). However, pencolide is a promising drug candidate with very low toxicity and better anitamoebic activity ( Mori et al., 2018 ). Hence, inhibiting the synthesis pathway of the endogenous reducing agent L-cysteine would hamper the survival of the parasite in the host gut.…”
Section: Cellular Drug Targetsmentioning
confidence: 99%